Associations Between Complement Components and Vitamin D and the Physical Activities of Daily Living Among a Longevous Population in Hainan, China - Zhang, Chi; Fu, Shihui; Zhao, Minghao; Liu, Deping; Zhao, Yali; Yao, Yao (Frontiers in Immunology, 2020)
Background: Vitamin D and complement components shared some common pathophysiological pathways in the musculoskeletal system, circulation, and metabolism, which were linked to physical function. It is hypothesized that serum complement components may interact with vitamin D in respect of the physical activities of daily living (PADLs). Objective: To investigate if serum complement components 3 (C3), complement components 4 (C4), and 25-hydroxyvitamin D [25(OH)D] associate with PADLs, and to examine whether the association between 25(OH)D levels and PADLs varies at different complement component levels among Chinese centenarians. Methods: This study was conducted in a group of population-based centenarians. PADLs were evaluated using the Barthel Index. Multiple regressions were used to analyze the associations among 25(OH)D, complements C3 and C4, and PADLs. Results: Among 943 participants, 672 (71.3%) had physical dependence (PD). After adjusting for potential confounders, serum 25(OH)D and C3 levels were positively correlated with PADLs, while C4 levels were negatively correlated with PADLs (Ps<0.05). Serum 25(OH)D levels significantly interacted with both C3 (P for interaction=0.033) and C4 (P for interaction=0.006) levels on PADLs. At lower complement component levels, the multivariate odds ratios (ORs) of the upper tertile of vitamin D for PD were 0.32 (95% CI: 0.18–0.55) in the C3 group and 0.29 (95% CI: 0.16–0.50) in the C4 group. At higher complement component levels, the ORs in the C3 and C4 groups were not statistically significant. Conclusions: In a group of population-based Chinese centenarians, we observed that serum complement C3 and 25(OH)D levels were positively associated with PADLs, while C4 was negatively associated with PADLs. The associations between 25(OH)D levels and PADLs were more pronounced in groups with lower serum complement component levels.